The Influence of E-office Utilization on the Realization of Paperless in the South Sulawesi Provincial General Election Supervisory Agency - Nurfadilla, Nurfadilla; Nasrullah, Muh.; Arhas, Sitti Hardiyanti (International Journal of Administration and Education, 2024)
This study aims to find out the overview of the use of e-office (SIPA), the description of the realization of paperless, and the influence of the use of e-office (SIPA) on the Paperless Embodiment. This study uses a quantitative approach with an associative type of research. In order to achieve the objectives of this research, data collection techniques were used including observation, questionnaires, and documentation. The population in this study is 52 employees with a total population of 48 employees with a sampling technique, namely using the Issac and Michael tables. The research data collected was then processed using descriptive and inferential statistical analysis to determine the Utilization of E-office (SIPA) for the Realization of Paperless in the South Sulawesi Provincial General Election Supervisory Agency. The results of the study show that the indicators used in each variable are concluded that the influence of the use of e-office (SIPA) is in the very good category and the realization of paperless is in the very good category. Based on the results of the product moment correlation analysis, the relationship between variables is very strong. Based on the results of a simple linear regression analysis, it was concluded that there was a significant unidirectional influence between the use of e-office (SIPA) on the realization of paperless in the South Sulawesi Provincial General Election Supervisory Agency.